Genotype-environment interaction on baby corn production - Gustavo André Simon; Carlos Alberto Scapim; Rânia Nunes Oliveira Moraes; Ludmilla Ribeiro da Rocha Gomes; Mauricio Carlos Kuki (Semina: Ciências Agrárias, 2020)
The phase of genotype evaluation for recommendation in different environments is seen as the key stage of breeding programs, in view of the importance of the genotype – environment interaction on the main traits. The objective of this study was to evaluate different field corn, popcorn, white corn, and sweet corn genotypes for their capacity of baby corn production and the genotype - environment interaction. Twenty-nine genotypes were evaluated, in a randomized complete block design with three replications. The experiments were performed in the main and second season in Rio Verde – GO and in the second season in Maringá – PR. Significant (p < 0.05) differences between the genotypes were observed for all evaluated traits. The genotype - environment interaction was only significant for mean ear diameter, prolificacy and ear yield, indicating a differentiated performance between genotypes in response to environmental variations. The predominance of the complex part of interaction on prolificacy and yield is emphasized. Although the baby corn harvest is performed even before ear fertilization, the results suggests that the variations in the traits related with babycorn production and quality are mainly influenced by genetic-environmental factors. The genotypes P30K64, HD 332, IPR 119, and IAC 125 obtained the highest means for the evaluated traits. The groups of white and field corn genotypes stood out for with a significantly better performance than the others, principally for ear yield.